ANALYSIS OF RECOVERY IN EXPORT IMPORT ACTIVITIES SUPPORTING ECONOMIC STABILITY BEFORE AND DURING PANDEMIC COVID-19 AT INDONESIA - Putri, Anggun; Rangkuty, Dewi Mahrani; Yusuf, Mohammad; Rusiadi, Rusiadi; Hasyyati, Zata (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
The purpose of this research is to see Export activities and Import in sustain stability economy before and During pandemic. Method which used are VAR and Difference Test. VAR research results that Export activities and Imports contribute optimally to each other in sustaining economic stability in Indonesia, good in period short, medium, nor long. Results FEVD that policy which used in activity Export ie in short term is done by Export itself, then in medium term and length of policy used in maintaining export activities namely by Export itself and influenced by Import. Then the FEVD results that the policy in maintaining imports in the short, medium and long term, namely by Import itself and followed by Export. Then the results of the Difference Test show that there is difference but no significant on Inflation and Exchange before and during the Covid-19 pandemic. If an error occurs in taking action against Exports and Imports can make the economy unstable. With thus in sustaining economic stability in Indonesia, the Government must more extra in taking Export performance policies and reducing Imports so that Growth Economy awake which will increase stability economy.